Materiality, Techniques and Society in Pottery Production The Technological Study of Archaeological Ceramics through Paste Analysis - Albero Santacreu, Daniel (De Gruyter, 2014)
Daniel Albero Santacreu presents a wide overview of certain aspects of the pottery analysis and summarizes most of the methodological and theoretical information currently applied in archaeology in order to develop wide and deep analysis of ceramic pastes. The book provides an adequate framework for understanding the way pottery production is organised and clarifies the meaning and role of the pottery in archaeological and traditional societies. The goal of this book is to encourage reflection, especially by those researchers who face the analysis of ceramics for the first time, by providing a background for the generation of their own research and to formulate their own questions depending on their concerns and interests. The three-part structure of the book allows readers to move easily from the analysis of the reality and ceramic material culture to the world of the ideas and theories and to develop a dialogue between data and their interpretation. Daniel Albero Santacreu is a Lecturer Assistant in the University of the Balearic Islands, member of the Research Group Arqueo UIB and the Ceramic Petrology Group. He has carried out the analysis of ceramics from several prehistoric societies placed in the Western Mediterranean, as well as the study of handmade pottery from contemporary ethnic groups in Northeast Ghana.